2021
DOI: 10.1039/d1ma00072a
|View full text |Cite
|
Sign up to set email alerts
|

Negative thermal expansion triggered anomalous thermal upconversion luminescence behaviors in Er3+/Yb3+-codoped Y2Mo3O12 microparticles for highly sensitive thermometry

Abstract: For the sake of overcoming the challenges of the optical thermometers with high sensitivity, we designed the Er3+/Yb3+-codoped Y2Mo3O12 microparticles with thermally enhanced upconversion (UC) emissions. Excited at 980 nm,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 43 publications
1
25
0
Order By: Relevance
“…As is shown, the studied compounds are made of corner-shared [YO 6 ] octahedrons and [MoO 4 ] tetrahedrons, in which the corner of the [YO 6 ] octahedron is shared by six [MoO 4 ] tetrahedrons, whereas the corner of the [MoO 4 ] tetrahedron is shared by four [YO 6 ] octahedrons. Notably, with elevating the temperature, the aforementioned structure is not stable and can be rotated, resulting in the lattice contraction and the enhanced ET from the sensitizer to the activator. , Figure b presents the X-ray diffraction (XRD) patterns of YMO:Tm 3+ /2 x Yb 3+ submicron particles. It is significant that these recorded diffraction profiles are the same, and they exhibit a perfect correlation with the orthorhombic YMO (JCPDS #28–1541), implying that the doping ions (Tm 3+ , Yb 3+ ) have little impact on the phase composition of YMO, and the synthesized submicron particles possess a pure orthorhombic phase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As is shown, the studied compounds are made of corner-shared [YO 6 ] octahedrons and [MoO 4 ] tetrahedrons, in which the corner of the [YO 6 ] octahedron is shared by six [MoO 4 ] tetrahedrons, whereas the corner of the [MoO 4 ] tetrahedron is shared by four [YO 6 ] octahedrons. Notably, with elevating the temperature, the aforementioned structure is not stable and can be rotated, resulting in the lattice contraction and the enhanced ET from the sensitizer to the activator. , Figure b presents the X-ray diffraction (XRD) patterns of YMO:Tm 3+ /2 x Yb 3+ submicron particles. It is significant that these recorded diffraction profiles are the same, and they exhibit a perfect correlation with the orthorhombic YMO (JCPDS #28–1541), implying that the doping ions (Tm 3+ , Yb 3+ ) have little impact on the phase composition of YMO, and the synthesized submicron particles possess a pure orthorhombic phase.…”
Section: Resultsmentioning
confidence: 99%
“…Evidently, the FIR values are hardly changed even after several cycled heating-cooling processes. Moreover, to quantitatively describe the reversibility of the studied samples, we utilized the following expression to calculate the repeatability ( R ) , herein, Q i and Q avg stand for the obtained FIR value and the average FIR value, respectively. Thus, the R values of I 700 / I 481 and I 700 / I 654 combinations are 94.2 and 94.8%, respectively, indicating that the prepared compounds possess splendid reversibility.…”
Section: Resultsmentioning
confidence: 99%
“…The application of A 2 M 3 O 12 materials in optical thermometry is a recent research topic (Zou et al, 2019;Lv et al, 2021). Er 3+ / Yb 3+ co-doped Y 2 Mo 3 O 12 microparticles have been proposed for this purpose.…”
Section: Applicationsmentioning
confidence: 99%
“…Er 3+ /Yb 3+ co-doped Y 2 Mo 3 O 12 shows rapid response, high spatial resolution and can be read without contact, providing advantages over traditional thermometers. Er 3+ /Yb 3+ co-doped Y 2 Mo 3 O 12 microparticles irradiated at 980 nm can have bright green emission, which becomes more intense with increasing temperature, presenting a mechanism for optical thermometry (Lv et al, 2021).…”
Section: Applicationsmentioning
confidence: 99%
“…In recent years, the phenomenon of luminescent thermal enhancement has been discovered and has attracted attention, and the excellent fluorescence properties have attracted extensive attention of researchers, bringing Dawn to overcome the thermal quenching of luminescent materials and optical ultrahigh temperature detection. [20][21][22] In 2014, Jiang et al discovered and reported the abnormal UC luminescence thermal enhancement of NaYF 4 :Yb 3+ /Er 3+ nanocrystals with less than 30 nm nanoparticles. 23 In 2019, Meijerink reported the thermal enhancement of NaY(WO 4 ) 2 :Yb 3+ /Er 3+ nanoparticles and Wang et al also reported on the thermal enhancement phenomenon caused by NTE in Yb 2 W 3 O 12 crystallites.…”
Section: Introductionmentioning
confidence: 99%